An Efficient Modal Control Strategy for the Active Vibration Control of a Truss Structure - Ricardo Carvalhal; Vicente Lopes Júnior; Michael J. Brennan (Shock and Vibration)
In this paper an efficient modal control strategy is described for the active vibration control of a truss structure. In this approach, a feedback force is applied to each mode to be controlled according to a weighting factor that is determined by assessing how much each mode is excited by the primary source. The strategy is effective provided that the primary source is at a fixed position on the structure, and that the source is stationary in the statistical sense. To test the effectiveness of the control strategy it is compared with an alternative, established approach namely, Independent Modal Space Control (IMSC). Numerical simulations show that with the new strategy it is possible to significantly reduce the control effort required, with a minimal reduction in control performance.